Lupus Vulgaris: A Rare Case of Cutaneous Tuberculosis (Bangladesh Medical Journal, 2014)
Lupus vulgaris is an extremely chronic, progressive form of cutaneous tuberculosis. The earliest description of lupus vulgaris was given by Erasmus Wilson in 1865. It usually occurs through contagious extension of the disease from underlying affected tissue or hematogenous or lymphatic spread. A 55 years male, non diabetic, non hypertensive, non smoker, got himself admitted into Dermatology and Venereology Department of DMCH with the complaints of multiple ulcerated lesions over the left lower thigh and upper leg including knee for 8 years. Histological sections of skin revealed multiple epithelioid granuloma, multinucleated giant cells and infiltration of lymphocytes with areas of fibrosis and ESR was 80 in 1st hour. The patient was treated with anti tubercular therapy and cured completely. DOI: http://dx.doi.org/10.3329/bmj.v41i2.18811 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 57-58